Utilization of Smart Technology on Performance Management in the Era of Society 5.0 : Literature Review Study - Elva Citra Sari; Tety Novriyanti Zebua; Muhammad Ikmal Husein Lubis; Robert Sanjaya Sembiring; Ritha F Dalimunthe Dalimunthe (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The integration of intelligent technology within performance management has emerged as a significant concern in the context of Society 5.0, wherein the synergy between humans and technology is essential for generating added value and enhancing productivity. Society 5.0 underscores the necessity for collaboration between advanced technological systems and societal frameworks, thereby necessitating an adaptive, data-driven, technology-based performance management system. This article offers a comprehensive literature review regarding the implementation of intelligent technology in performance management, with particular emphasis on technologies such as artificial intelligence (AI), the Internet of Things (IoT), big data, and analytics, all aimed at improving the efficiency and effectiveness of organizational performance. Through an examination of recent scholarly works, this article delineates the factors that influence the adoption of smart technology, the challenges encountered, and the prospective advantages for human resource management and organizational objectives. The findings indicate that smart technology not only enhances the performance measurement process but also facilitates accelerated and more precise decision-making based on real-time data. Nevertheless, the successful adoption of this technology necessitates readiness in digital infrastructure, transformation of organizational culture, and the presence of qualified human resource competencies. This article seeks to provide valuable insights for academics, practitioners, and policymakers in devising strategies for the implementation of smart technology within the Society 5.0 framework to promote sustainable improvements in organizational performance.